Nurse Index Satisfaction at Hospital with Nurse Profession, Training, Nurse Assessment and Ethic Implementation in Pandemic Situation - Erick Prawira Suhardhi; Ascobat Gani (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Introduction. Pandemic Covid-19 situation in Indonesia since March 2021, make hospitals to have adaption with condition. Therefore, there is un satisfaction for nurse profession, training, nurse assessment and ethical in emergency, this is known by pre survei in emergency. This research was aimed to study about nurse satisfaction in pandemic area, and see pandemic effect to nurse satisfaction, topic research is satisfaction for nurse profesion, training, nurse assesment and ethical nurse. Methods. Research method for this research is descriptive quantitative, where research use fact, situation and variable happen when the research on going. instrument used in this research is quisoner, sample used is nurse which work in Hospital X, Tangerang district with total sample 151 nurses. Results. Nurse satisfaction preview in hospitals X, Tangerang district is more than 90% nurses satisfied with profession of nurses, training more than, nurse assessment and ethical of nurse. Conclusion. All the nurse satisfied with their profession, training, assesment and ethical implementation, there is improvement room to reduce blame culture in nurse division and implement just culture in nurse division.